Japonia i jej wzrost gospodarczy - Stawicka, Magdalena; Piotrowski, Tomasz (Japan and Economic Growth, 2007)
Japan is considered to be still in transition from industrial into post-industrial era. This fact influences general economic situation of the country. This paper tries to analyze the rationale of its current position by covering most significant events that occurred throughout economic history and had considerable impact.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (14); 2007; nr 1164, s. 208-220